2002
DOI: 10.1111/j.1349-7006.2002.tb01250.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Hepatocellular Adenomas and Carcinomas Associated with Fibrosis in C57BL/6J Male Mice Given a Choline‐deficient, L‐Amino Acid‐defined Diet

Abstract: Development of hepatocellular carcinomas in rats caused by a choline-deficient, L-amino aciddefined (CDAA) diet, usually associated with fatty liver, fibrosis, cirrhosis and oxidative DNA damage, has been recognized as a useful model of hepatocarcinogenesis caused by endogenous factors. In the present study, in order to further explore involved factors and genes, we established an equivalent model in spontaneous liver tumor-resistant C57BL/6J mice. Six-week-old males and females were continuously fed the CDAA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 42 publications
2
83
0
Order By: Relevance
“…The exact mechanism underlying the development of HCC in association with NASH remains unclear; therefore, establishment of improved animal models that mimic human disease are important for a better understanding of the microenvironmental factors that lead to tumor progression in the liver. It has been suggested, through the use of dietary mouse models, that obesity-related hepatic steatosis might increase the susceptibility to development of malignancy in the liver (8,41). More recently, we (25) demonstrated that long-term high-fat diet (HFD) loading, which can induce obesity, was sufficient to induce NASH and liver tumorigenesis in C57Bl/6 mice, a finding that has also been corroborated by other studies (14,29,41).…”
supporting
confidence: 76%
“…The exact mechanism underlying the development of HCC in association with NASH remains unclear; therefore, establishment of improved animal models that mimic human disease are important for a better understanding of the microenvironmental factors that lead to tumor progression in the liver. It has been suggested, through the use of dietary mouse models, that obesity-related hepatic steatosis might increase the susceptibility to development of malignancy in the liver (8,41). More recently, we (25) demonstrated that long-term high-fat diet (HFD) loading, which can induce obesity, was sufficient to induce NASH and liver tumorigenesis in C57Bl/6 mice, a finding that has also been corroborated by other studies (14,29,41).…”
supporting
confidence: 76%
“…37 To examine whether Bid deletion in hepatocytes also regulates carcinogenesis in NAFLD, the fastest growing cause of HCC and a disease characterized by increased hepatocyte apoptosis, we used a human pathophysiologically relevant model of disease induced by feeding mice a CDAA defined diet that induces in a time-dependent manner the various stages of NAFLD from hepatic steatosis to steatohepatitis to HCC. 17 Our findings demonstrate that Bid Δhep was protected from HCC development after 48 weeks on this diet in a process that was independent of lipid overloading of the liver and associated with a decrease in hepatocyte apoptosis.…”
Section: Discussionmentioning
confidence: 52%
“…17 University of California San Diego (USCD) Institutional Animal Care and Use Committee approved protocols. All mice were maintained in filter topped cages with free access to food and water at UCSD according to the NIH guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…A choline-deficient l-amino acid-defined diet is similar to the MCD diet, but in addition, it induces obesity and insulin resistance. In the long term, this model is important for NAFLD, NASH, and HCC studies because it promotes liver tumor formation associated with liver fibrosis (78).…”
Section: Diet-based Modelsmentioning
confidence: 99%